Aerodynamic models for Darrieus-type straight-bladed vertical axis wind turbines - Islam, Mazharul; Ting, David; Fartaj, Amir (Elsevier, 2008)
Since ancient past humans have attempted to harness the wind energy through diversified means and vertical axis wind turbines (VAWTs) were one of the major equipment to achieve that. In this modern time, there is resurgence of interests regarding VAWTs as numerous universities and research institutions have carried out extensive research activities and developed numerous designs based on several aerodynamic computational models. These models are crucial for deducing optimum design parameters and also for predicting the performance before fabricating the VAWT. In this review, the authors have attempted to compile the main aerodynamic models that have been used for performance prediction and design of straight-bladed Darrieus-type VAWT. It has been found out that at present the most widely used models are the double-multiple streamtube model, Vortex model and the Cascade model. Each of these three models has its strengths and weaknesses which are discussed in this paper.